Here comes Santa paws - Berenson, Laurien (Berenson, Laurien. Melanie Travis mystery., 2019)
As Melanie attempts to deck the halls in a house overrun by pampered Poodles, her event planner friend, Claire, is busy playing Santa<U+2014>beard and belly not included<U+2014>for the wealthiest clientele on Connecticut<U+2019>s Gold Coast. A personal shopper gig in the affluent town of New Canaan seems like business as usual. Except Claire<U+2019>s stylish stint comes at a higher price than she bargains for when she stumbles over her newest customer<U+2019>s dead body on the job. Named a prime suspect for murder, she begs for Melanie<U+2019>s help, then vanishes like cookies and milk on Christmas Eve . . . Determined to track down Claire, Melanie and her nosy Aunt Peg dash into a dizzying investigation that leads to even more questions. Why was homicide victim Lila Moran, a secretive woman with an untraceable past, permitted to live on a well-known socialite-turned-recluse<U+2019>s private estate, and is Claire keeping her own incriminating secrets under wraps? Now, with a grinchy New Canaan detective on their case and disturbing clues piling up like presents beneath the tree, the crime-solving duo must rein in a sinister Kris Kringle before they<U+2019>re the next ones on someone<U+2019>s deadly wish list . . .